Comparing transcriptomes of distant organisms: models of gene expression 2 - Gerstein, Mark (Henry Stewart Talks, 2017)
Histone modification (HM) models relating gene expression to promoter activity, Building a universal model for human, worm and fly, Similarly constructed transcription factor (TF) binding models